Lipophilic magnetite nanoparticles coated with stearic acid: A potential green and low cost way to improve thermal stability and tribological properties of fully formulated low viscosity engine oils. (June 2020) - Zuin, André; Cousseau, T.; Sinatora, A.; Toma, H.E.
Abstract: Lipophilic nanoparticles of magnetite (d ≈ 10 nm) functionalized with stearic acid (MagNP) were tested as additive in modern engine oil with low viscosity and high additization. Its thermal and tribological properties were evaluate using TG/DTA and a high frequency reciprocating tribometer, respectively. All tests were performed with the neat oil and the oil+MagNP. The analysis showed that MagNP: i) improved thermal stability of the engine oil; ii) kept friction values lower and more stable; iii) drastically reduce wear marks; iv) improved the deposition of additives from the lubricating oil onto the worn surface. Highlights: MagNP into SAE0W20 oil increased its thermal stability and improved the oil retention. MagNP into SAE0W20 oil reduced the friction values mostly during load step transition. MagNP into SAE0W20 oil reduced significantly the wear marks. MagNP into SAE0W20 oil promoted the concentration of the additives in the contact.